Does public segmentation matter in crisis communication? The interplay between public segmentation and crisis response strategies. (29th April 2021) - Wen, Taylor Jing; Li, Jo-Yun; Song, Baobao
Abstract : Purpose: This study situates in the context of Chipotle's food safety issue and seeks to understand how their primary customers perceive their crisis response messages after learning of the outbreaks. The current study incorporates the framework of situational crisis communication theory (SCCT; Coombs, 2007) and public segmentation model (Rawlins, 2006) to understand the effectiveness of crisis response messages. It aims to examine the role of public segmentation in situational crisis communication and investigate the effects of three crisis response strategies according to SCCT on different public segments. Design/methodology/approach: The SCCT provides guidelines for understanding the effectiveness of different crisis response strategies. The current study showcases the importance of public segmentation in the SCCT model through the lens of stakeholder theory. A 3 (crisis response strategy: deny, diminish, rebuild) × 4 (public segment: advocate, dormant, adversarial, apathetic) factorial experiment was conducted. Findings: The findings suggest that advocate public expressed more positive evaluation about the company when exposed to rebuild and deny strategies. Both dormant and adversarial stakeholders reported positive responses on rebuild and diminish strategies. However, no difference was found among apathetic public. Originality/value: The researchers attempt to make a modest contribution in this direction by reporting results from an empirical experiment that examined the effects of crisis response strategies on different public segments. The findings suggest an effective message tailoring approach to target different public segments. Thus, the results of this study are expected to benefit relevant corporations and public relations practitioners.